The Labor-Managed Firm: Permanent or Start-Up Subsidies?. Issue 4 (2nd October 2017) - Groot, Loek; van der Linde, Daan
Abstract: We explore a new argument that seeks to explain the near absence of the labor-managed firm or cooperative, despite a range of inefficiencies attributed to the present-day capitalist firm. We derive the crucial condition for the emergence of labor-managed firms and show that it is unduly restrictive from an efficiency point of view. The policy implication is that public intervention to promote labor-managed firms should primarily be in the form of start-up subsidies rather than in providing permanent tax subsidies.